Pengaruh Pembiayaan Produktif dan Konsumtif Perbankan Syari'ah Terhadap Pertumbuhan Ekonomi Di Indonesia Periode 2013-2017 - Sudrajat, Anton; Sodiq, Amirus (Universitas Islam Negeri Sunan Kudus, 2017)
In order for a country’s economy to grow needed economic resources one of which is the capital that comes from banking. The capital is used for production purposes so that it can increase productivity and in turn can cause economic growth of a country. The purpose of this study is to determine the effect of productive financing and consumptive financing of sharia banking to economic growth in Indonesia. The results showed that partially productive financing of sharia banking has a significant effect on economic growth in Indonesia. While consumptive financing of sharia banking has no significant effect on economic growth in Indonesia. Simultaneously, productive and consumer financing of sharia banking has a significant effect on economic growth in Indonesia with 91.3% influence.